Aktivitas Antioksidan Dan Uji Organoleptik Teh Celup Batang Dan Bunga Kecombrang Pada Variasi Suhu Pengeringan - Rohkyani, Ida, Dra. Titik Suryani, M.Sc (2015)
Tea is a beverage that is often consumed by Indonesian people because it tastes fresh, made from tea leaves, one alternative has the tea ingredients kecombrang flower and stem. Kecombrang Stem and flower contain alkaloids, saponins, tannins, phenolics, flavonoids, steroids, vitamins, minerals and glycosides as an antimicrobial and antioxidant. The purpose of this research was to know the content of antioxidant activity and organoleptic test of quality tea bag kecombrang with temperature drying variations. The methods design was completely randomized design with two factors: The first factor: tea material: Stem (W1), flower (W2) and the second factor: drying temperature 60oC (T1), 75oC (T2) and 85oC (T3). The results showed that the highest antioxidant activity in the treatment of T1W2 (flower tea material at 65oC) was 66.43% and the lowest antioxidant activity in treatment T3W1 (stem tea material at 85oC) was 56.76%. The Quality of tea has cloudy white. color and pink, sour taste, less fragrant odor.